(untitled) (International Journal of Engineering and Computer Science, 2018)
: Now a days in this e-world most of the business totally related to the process mining trends, it is been generated and checks the process flow in terms of changes in the whole system. Here a few process mining techniques are used to analyze the changes in the drifts, this drifts may be changes according to the process and it can be sudden change, gradually change or the random change .This changes can be visualized by using the Rapid Miner tool, in that a ProM framework is used to get the better Results. Not only it tracks the change it also finds the localization in the business Process. Here Feature Extraction and Generate Population method is used to find the relationship among the activities. Event logs are used to establish the process flow